Intellectual Capital and Corporate Social Responsibility on Stock Returns - Ameliana, Yana; Lantara, Niniek F; Arfah, Aryati; Arif, Muhammad (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
This study aimed to determine the effect of intellectual capital and corporate social responsibility on stock returns in manufacturing companies listed on the Indonesia Stock Exchange. The type of data used in this study is quantitative data in the form of values or numbers obtained from financial reports. The source of data in this research is secondary data. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange, totaling 17 companies. Using a purposive sampling method, the total sample in this study is 51 data from 17 companies. The data in this study will be tested with several stages of testing, namely descriptive statistical tests, classic assumption tests (normality test, heteroscedasticity test, multicollinearity test), and testing of all hypotheses through the partial test (t test), simultaneous test and coefficient test determination. The results of this study indicate that intellectual capital and corporate social responsibility have a positive and significant effect on stock returns in manufacturing companies listed on the Indonesia Stock Exchange (IDX). This means that the increasing value of intellectual capital and corporate social responsibility, the stock return will also increase.